Comprehensive assessment of dietary micronutrient profiles and their effects on hemoglobin levels and anemia: provincial nutrition and health monitoring - Wang, Yan; Lin, Yun; Lv, Ye; Jin, Yiyuan; Gao, Hua; Gao, Sihai; Shentu, Pingping; Xing, Chao; Chen, Yan; Zhao, Shiguang; Cong, Ying; Liu, Guangtao; et al. (Frontiers in Nutrition, 2025)
BackgroundMicronutrients play a major role in regulating public health. Inadequate intake of micronutrients is a frequent and potentially hazardous occurrence that may lead to the development of common pathologies, such as anemia, a widespread health concern. This study aimed to estimate dietary micronutrient intake inadequacies and to investigate the association between micronutrients and hemoglobin (Hb) levels or anemia.MethodsThis study employed a cross-sectional design, including 15,810 participants. The questionnaire used in this study consisted of sections on demographic characteristics, lifestyles, dietary assessment, and disease history. Dietary intake information was collected using the 3-day 24-h dietary recall method. Hemoglobin levels were measured using the colorimetric method. The individual effect of micronutrients on Hb and anemia was evaluated using restricted cubic splines (RCS) and multiple logistic regression. The combined effect was assessed by weighted quantile sum regression (WQSR).ResultsThe study included 7,570 male and 8,240 female participants from a representative survey of Zhejiang Province, China. The prevalence of anemia was 12.2%. The mean Hb level in the overall population was 139 (15.7) g/L. Specifically, the mean Hb level was 142 (12.8) g/L in normal participants and 114 (11.2) g/L in anemic participants. Inadequate dietary intake rate for riboflavin (88.1%), vitamin E (87.6%), and calcium (81.6%) was high, while the rate of inadequate dietary intake for iron (13.3%), iodine (7.06%), and selenium (3.15%) was low. The influencing factors of anemia included age, sex, living area, income, smoking status, physical activity, body mass index (BMI), and diabetes. A linear dose–response positive relationship between thiamin, vitamin C, and selenium and Hb was found among women. According to the results of multiple logistic regression, thiamin [odds ratio (OR): 0.81; 95% confidence interval (CI): 0.67–0.97] and selenium (OR: 0.93; 95% CI: 0.88–0.99) were significantly associated with a decreased risk of anemia among women.ConclusionThe prevalence of inadequate micronutrient intake was generally high, and micronutrient intakes had a significant protective effect against anemia, suggesting that interventions should be conducted to overcome the micronutrient intake inadequacies.